Pelatihan Pemasaran Digital untuk Meningkatkan Pendapatan Pelaku UMKM Desa Dasan Baru - Saepul Pahmi; Sri Ayu Febrianti; Rini Yuliandar (Yayasan Daarul Huda Kruengmane, 2026)
This Community Service Program (PKM) aims to enhance the knowledge and skills of Micro, Small, and Medium Enterprise (MSME) actors in Dasan Baru Village in implementing digital marketing strategies, optimizing the use of social media, and developing content marketing. The training was conducted using a classical (classroom-based) approach at the Dasan Baru Village Office hall and was complemented by interactive question-and-answer sessions with participants. The implementation methods included a pre-test, material delivery by four presenters, hands-on practice in digital marketing analysis, and a post-test as an evaluation tool. The activity was carried out smoothly with a total of 21 participants and was considered effective in improving the digital literacy of MSME actors. The results indicate an increase in participants’ understanding of digital marketing strategies, social media utilization, and content creation techniques. The training also encouraged participants to actively utilize digital platforms to expand market reach and increase business revenue. The implication of this program is that participants gained a better understanding of how to conduct digital marketing and effectively use social media to enhance product sales.